1995
DOI: 10.1109/72.377984
|View full text |Cite
|
Sign up to set email alerts
|

The high-order Boltzmann machine: learned distribution and topology

Abstract: In this paper we give a formal definition of the high-order Boltzmann machine (BM), and extend the well-known results on the convergence of the learning algorithm of the two-order BM. From the Bahadur-Lazarsfeld expansion we characterize the probability distribution learned by the high order BM. Likewise a criterion is given to establish the topology of the BM depending on the significant correlations of the particular probability distribution to be learned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…where D[q, p(ξ p )] is treated as a function of BM's parameters ξ p and λ is the learning rate. As shown in [32], the gradient descent method converges to the minimum of the divergence with proper choices of λ, and hence achieves the projection point Γ B (q). Last, we show that the mixed coordinates [ζ xh ] Γ B (q) in Equation ( 20) is exactly the convergence point of the ML learning for BM.…”
Section: Appendix H Proof Ofmentioning
confidence: 95%
“…where D[q, p(ξ p )] is treated as a function of BM's parameters ξ p and λ is the learning rate. As shown in [32], the gradient descent method converges to the minimum of the divergence with proper choices of λ, and hence achieves the projection point Γ B (q). Last, we show that the mixed coordinates [ζ xh ] Γ B (q) in Equation ( 20) is exactly the convergence point of the ML learning for BM.…”
Section: Appendix H Proof Ofmentioning
confidence: 95%
“…Let be a positive probability function on that admits a factorization (2) where 1 . It can be shown that the probability function can be written as through a consensus function where the weights are determined and the set of weighted connections is (3) We name the hypergraph of the factorization (2). In this notation is the set of indexes of the variables in .…”
Section: Structure Of the Hobm From Conditional Independencesmentioning
confidence: 99%
“…T HE conventional Boltzmann machine (BM) [1], [9], as well as the high-order Boltzmann machine (HOBM) [15], [3], is a technique whose purpose is, in its fundamental formulation, to describe and model probability distributions defined on a set of binary random variables.…”
Section: Introductionmentioning
confidence: 99%
“…Topologies are widely used in the research field of machine learning and cybernetics (see e.g. Acencio and Lemke 2009;Albizuri et al 1995;Carr et al 2009;Choudhury and Zaman 2006;Kall et al 2004;Koretelainen 1999Koretelainen , 2001Li et al 2003;Thierens and Vercauteren 1991). For example, Koretelainen (1999Koretelainen ( , 2001 used topologies to detect dependencies of attributes in information systems with respect to gradual rules.…”
Section: Introductionmentioning
confidence: 99%